Restructuring Interlinked With Employer and Corporate Branding Amidst COVID-19: Embodying Crowdsourcing - Sabir, Raja Irfan; Nazri, Mohammad; Majid, Muhammad Bilal; Mahmood, Hamid; Abbas, Khurram; Bano, Sobia (Frontiers in Psychology, 2022)
The COVID-19 pandemic is an unprecedented time in history. Surrounding this pandemic are many enormous uncertainties across the globe. Severe consequences have assessed for the incomes of almost 84% of employers and 68% of self-employed who are working and living in countries that are or have went through a phase of closing workplaces. Similarly, the global rate of unemployment is also expected to be increased in the coming years as 54% of employers worldwide are running their businesses in the hardest-hit sectors. All of these clearly show the uneven impact of the Coronavirus crisis (COVID-19) which will remarkably compound already present inequalities, difficulties, and vulnerabilities. The economic ramifications for 186 countries under the crunch of the COVID-19 pandemic is also considered tremendous for Pakistan. The core aim of this research was to test a new conceptual framework depicting the ramifications of restructuring processes carried out by management for their organizations amidst the COVID-19 pandemic on an Institute’s reputation as an employer brand. It also investigates the impact of perceived restructuring on a corporate brand promise made by the university or institute from the viewpoints of other key stakeholders and potential job seekers. The current study had proposed four hypotheses and according to the results of Structural Equation Modeling, the direct hypothesis based upon the relationship between restructuring and employer branding has been rejected. This study shows that restructuring and employer branding has a negative and insignificant effect on each other. The second direct hypothesis of the study that measures the effect of restructuring on corporate branding has been accepted. A corporate brand is a kind of a hub and it considers how an institute treats and deals with all of its stakeholders. It is different from employer brand as the perceptions of employees were the main focus. So, according to the results restructuring did not cause massive damage to the overall outlook of the institute. Furthermore, for the purpose of mediation analysis, the maximum likelihood method by bootstrapping was adopted to test the indirect hypotheses of the study. Crowdsourcing was introduced as a mediator in this study with restructuring, employer, and corporate brand all together in one framework, which is the novel aspect of this study. There are two indirect hypotheses and according to the results both of them did not show any insignificant results. Firstly, the study analyzed mediation among crowdsourcing, restructuring, and employer branding which was fully accepted as the results showed full mediation between these constructs. Secondly, the study analyzed mediation among crowdsourcing, restructuring, and corporate branding which was partially accepted as results showed partial mediation between these constructs.